Analysis of human resources management practices: the impact of training on performance efficiency of employees of Akhmet Yassawi University - Abdrasilov, B.; Kudaibergenov, Zh.; Kelesbayev, D.; Baimaganbetov, S. (BUKETOV BUSINESS REVIEW, 2021)
Object: Human resources management (HRM) provides the necessary guidance in order to reach the most efficient result through the most effective way. This paper aims to determine the relation between the descriptive characteristics and HRM practices, and the impact of training practices on the performance of employees. Methods: The authors used the questionnaire method in collecting data and the 5-point Likert system to assess them. Then, the obtained data were analyzed by using SPSS Statistics program. The authors applied the factor analysis, T-test, ANOVA test, regression analysis methods. Findings: This paper determines the impact of training practices, namely, the satisfaction factor and motivation factor, to the performance efficiency of the employees. When the satisfaction factor increases by one unit, the performance level will decrease by 0.145 units. There is a positive correlation between the performance and the motivation factor. If the motivation factor increases by one unit, performance level will also increase by 0.413 units. Conclusion: Training activities increase the professional and technical knowledge of the employees as well as improve their abilities and corporate culture. Thus, it is necessary to provide a working environment where employees can continuously learn and develop themselves through training.